2021
DOI: 10.1590/1413-81232021263.07552019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prevalence of anti-N-methyl-d-aspartate receptor IgG antibodies in early stages of psychosis

Abstract: We investigated the feasibility of including plasma anti-NMDAR antibody screening in the assessment of first-episode psychosis patients in an early intervention programme in the Southern hemisphere. Anti-NMDAR IgG antibodies were assessed by ELISA in 166 patients (64.0% men), 166 matched population-based controls and 76 patients’ siblings (30.3% men). Fisher’s exact test and ANOVA were performed. Positive anti-NMDAR antibody patients were more often observed in bipolar disorder (10.0%) than schizophrenia (2.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Another issue seems to be the presence of CSF-NMDAR antibodies, as such CSF-NMDAR autoantibodies are associated with a higher percentage of patients suffering from psychiatric symptoms [ 42 ]. A recent investigation demonstrated that patients displaying psychotic symptoms are not the most frequent patients presenting NMDAR antibodies, as they were most frequently detected in conjunction with bipolar disorder (10%) and less often but still frequently identified accompanying schizophrenia (2.4%) or depression (3%) [ 43 ]. An investigation by Pearlman and Najjar [ 44 ] delivered similar results, demonstrating that schizophrenia, schizoaffective disorder, bipolar or major depressive disorder are associated with a three-times higher risk of having elevated NMDAR antibody titers than healthy controls.…”
Section: Pathogenic Role Of Nmdar Antibodies In Psychiatric Disordersmentioning
confidence: 99%
“…Another issue seems to be the presence of CSF-NMDAR antibodies, as such CSF-NMDAR autoantibodies are associated with a higher percentage of patients suffering from psychiatric symptoms [ 42 ]. A recent investigation demonstrated that patients displaying psychotic symptoms are not the most frequent patients presenting NMDAR antibodies, as they were most frequently detected in conjunction with bipolar disorder (10%) and less often but still frequently identified accompanying schizophrenia (2.4%) or depression (3%) [ 43 ]. An investigation by Pearlman and Najjar [ 44 ] delivered similar results, demonstrating that schizophrenia, schizoaffective disorder, bipolar or major depressive disorder are associated with a three-times higher risk of having elevated NMDAR antibody titers than healthy controls.…”
Section: Pathogenic Role Of Nmdar Antibodies In Psychiatric Disordersmentioning
confidence: 99%